Review article: Still room for debate on China and the Great Divergence - Niv Horesh (Essays in Economic & Business History (EEBH), 2023)
One of the most stimulating debates in economic history over the last two decades has been that surrounding the so-called "Great Divergence", namely precisely when the Asian economies fell behind Europe. To date much of that debate has hinged on real wage data. This article highlights and contextualizes evidence from the extant literature that both offsets and supports the notion that living standards in China, as one key component of the Asian Divergence, were similar to Europe as recently as 1800. The article also identifies where more research is necessary so as to make a more robust judgement in the "Great Divergence" debate. To achieve these aims, the article delves into evidence on taxation, interest rates, market integration, standards of living, joint-stock enterprise, cartography and law and finance. China lies at the center of these arguments, but other Asian economies are observed.
Keywords: 330; Great Divergence; China; Taxation; Interest Rates; Indebtedness; Joint-Stock Enterprise; Cartography; Law